THE INFLUENCE OF PROFESSIONAL COMMITMENT AND AUDIT EXPERIENCE ON EXTERNAL AUDITORS' ETHICAL DECISION MAKING IN PUBLIC ACCOUNTING OFFICE IN SURABAYA CITY - Alif Faruqi Febri Yanto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This research aims to examine the relationship between professional commitment, audit experience, and ethical decision making of external auditors in Surabaya, Indonesia. The study utilized a quantitative descriptive research design with purposive sampling of public accountants who have more than one year of experience and are entitled to sign accountants' reports. The Partial Least Square 3.0 analysis model was used to analyze the data. The findings of the hypothesis testing reveal that professional commitment and audit experience partially have a positive effect on the ethical decision-making of external auditors. The study highlights the importance of professional commitment and audit experience in shaping the ethical decision-making process of auditors.